Inovasi Pembuatan Cookies dengan Pemanfatan Tepung Sorgum dan Tepung Kacang Hijau (Vigna Ridiata) - Ervina Dewi Andriati; Ita Fatkhur Romadhoni; Niken Purwidiani; Andika Kuncoro Widagdo (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2024)
This research aims to develop innovations in the manufacture of cookies with the addition of sorghum flour and mung bean flour (Vigna radiata) as the main ingredients. Sorghum flour was chosen because it has a high fiber content, is gluten-free, and rich in antioxidants. Mung bean flour was chosen because it is rich in vegetable protein, fiber, vitamins, and minerals that are important for health. The main objective of this study was to evaluate the effect of adding both types of flour on the physicochemical characteristics, texture, taste, and color of cookies. The research method involved the formulation of various proportions of sorghum flour and mung bean flour, as well as organoleptic tests to assess consumer preferences. Tests were conducted using chemical analysis to determine nutrient content as well as sensory tests to assess texture, taste, and color attributes. The results showed that the addition of sorghum flour and mung bean flour can increase the nutritional content of cookies, especially in terms of fiber and protein.In addition, the combination of these two flours provides a crispier texture and distinctive flavor, which is different from conventional cookies. Overall, this innovation offers a healthier alternative for consumers without compromising the sensory quality of the cookies. The use of sorghum flour and mung bean flour in making cookies not only increases the nutritional value but also fulfills the market need for healthier food products. These findings make an important contribution to the development of functional food products that can be accepted by various groups of people.